PENDAMPINGAN PENDIDIKAN DAN PELATIHAN PEMASARAN DIGITAL BERBASIS MEDIA SOSIAL INSTAGRAM - Artika Arista; Rudhy Ho Purabaya; Ika Nurlaili Isnainiyah (JMM (Jurnal Masyarakat Mandiri), 2023)
Abstrak: Peningkatan kapasitas dan daya saing industri semakin ketat mengingat pesatnya perkembangan penggunaan teknologi digital di berbagai industri. Oleh karena itu, pengabdi tertarik untuk melakukan pengabdian kepada masyarakat melalui kegiatan pendampingan pendidikan dan pelatihan pemasaran rumput laut berbasis digital pada masyarakat dan desa Tengkurak. Kegiatan ini bertujuan untuk mengoptimalkan potensi desa melalui kegiatan pendampingan pendidikan dan pelatihan masyarakat dalam upaya meningkatkan daya saing pemasaran produk komoditas serta peningkatan penerapan IPTEK bagi masyarakat. Kegiatan pemberdayaanmelibatkan 10 peserta yang terdiri dari masyarakat pengiat industri dan umum. . Metode awal sebelum pengajuan proposal yaitu dilakukan observasi ke Desa Tengkurak pada 4 Februari 2022. Kegiatan pengabdian dilanjutkan dengan pembuatan (1) video tutorial; dan (2) modul Pemasaran Digital Berbasis Media Sosial Instagram. Berdasarkan hasil evaluasi dari wawancara peserta, diketahui bahwa pemahaman awal masyarakat hanya 30%, kemudian terdapat peningkatan sebesar 40% menjadi 70% setelah mengikuti video tutorial dan modul. Rencana tindak lanjut dari tim pengabdi adalah pendampingan berkelanjutan dengan menyesuaikan dengan perkembangan teknologi.Abstract: Increasing the capacity and competitiveness of the industry in the face of increasingly fierce competition in the global market has become very important given the rapid development of the use of digital technology in various industries. Therefore, the pengabdi is interested in conducting community service through educational assistance and training activities for digital-based seaweed marketing in the community and Tengkurak village. This activity aims to optimize the potential of the village through community education and training assistance activities in an effort to increase the competitiveness of commodity product marketing and increase the application of science and technology for the community. Therefore, the service team is interested in conducting digital-based marketing education assistance as a concrete manifestation of the collaboration program between the Dean of the Faculty of Computer Science UPN Veteran Jakarta and the Head of the Office of Empowerment activities involving 10 participants consisting of industrial and general activists. Communities and villages of Serang Regency, especially Tengkurak Village, Tirtayasa District. The initial method before submitting the proposal was observation to Tengkurak Village which began on February 43, 2022. The service activity was continued by making (1) video tutorials; and (2) Instagram social media-Based Digital Marketing modules. Based on the evaluation results from participant interviews, it is known that the initial understanding of the community was only 30%, then there was an increase of 40% but increased to 70% after attending video tutorials and modules, there was an increase of 40%. The follow-up plan that can be done by the service team is continuous assistance by adjusting to technological developments.